BOTANY OF FIELD CROPS-1 Cereals,Pulses and Oilseeds Crops - J.S. Nanda; P.K. Agrawal (Ludhiana Kalyani)
In the book over 100 important field crops have been covered,besides a chapter each on origin of agriculture and classification of field crops
Cerials Pulses Oilseed
Keywords: Cerials, Pulses, Oilseed